Pleiotropic Effects of IL-33 on CD4+ T Cell Differentiation and Effector Functions - Alvarez, Fernando; Fritz, Jörg H.; Piccirillo, Ciriaco A. (Frontiers in Immunology, 2019)
IL-33, a member of the IL-1 family of cytokines, was originally described in 2005 as a promoter of type 2 immune responses. However, recent evidence reveals a more complex picture. This cytokine is released locally as an alarmin upon cellular damage where innate cell types respond to IL-33 by modulating their differentiation and influencing the polarizing signals they provide to T cells at the time of antigen presentation. Moreover, the prominent expression of the IL-33 receptor, ST2, on GATA3+ T helper 2 cells (TH2) demonstrated that IL-33 could have a direct impact on T cells. Recent observations reveal that T-bet+ TH1 cells and Foxp3+ regulatory T (TREG) cells can also express the ST2 receptor, either transiently or permanently. As such, IL-33 can have a direct effect on the dynamics of T cell populations. As IL-33 release was shown to play both an inflammatory and a suppressive role, understanding the complex effect of this cytokine on T cell homeostasis is paramount. In this review, we will focus on the factors that modulate ST2 expression on T cells, the effect of IL-33 on helper T cell responses and the role of IL-33 on TREG cell function.